Facilitating safety evaluation in maternal immunization trials: a retrospective cohort study to assess pregnancy outcomes and events of interest in low-risk pregnancies in England - Riley, Megan; Lambrelli, Dimitra; Graham, Sophie; Henry, Ouzama; Sutherland, Andrea; Schmidt, Alexander; Sawalhi-Leckenby, Nicola; Donaldson, Robert; Stoszek, Sonia K. (BMC pregnancy and childbirth, 2022)
Background Maternal characteristics like medical history and health-related risk factors can influence the incidence of pregnancy outcomes and pregnancy-related events of interest (EIs). Data on the incidence of these endpoints in low-risk pregnant women are needed for appropriate external safety comparisons in maternal immunization trials. To address this need, this study estimated the incidence proportions of pregnancy outcomes and pregnancy-related EIs in different pregnancy cohorts (including low-risk pregnancies) in England, contained in the Clinical Practice Research Datalink (CPRD) Pregnancy Register linked to Hospital Episode Statistics (HES) between 2005 and 2017. Methods The incidence proportions of 7 pregnancy outcomes and 15 EIs were calculated for: (1) all pregnancies (AP) represented in the CPRD Pregnancy Register linked to HES (AP cohort; N = 298 155), (2) all pregnancies with a gestational age (GA) ≥ 24 weeks (AP24+ cohort; N = 208 328), and (3) low-risk pregnancies (LR cohort; N = 137 932) with a GA ≥ 24 weeks and no diagnosis of predefined high-risk medical conditions until 24 weeks GA. Results Miscarriage was the most common adverse pregnancy outcome in the AP cohort (1 379.5 per 10 000 pregnancies) but could not be assessed in the other cohorts because these only included pregnancies with a GA ≥ 24 weeks, and miscarriages with GA ≥ 24 weeks were reclassified as stillbirths. Preterm delivery (< 37 weeks GA) was the most common adverse pregnancy outcome in the AP24+ and LR cohorts (742.9 and 680.0 per 10 000 pregnancies, respectively). Focusing on the cohorts with a GA ≥ 24 weeks, the most common pregnancy-related EIs in the AP24+ and LR cohorts were fetal/perinatal distress or asphyxia (1 824.3 and 1 833.0 per 10 000 pregnancies), vaginal/intrauterine hemorrhage (799.2 and 729.0 per 10 000 pregnancies), and labor protraction/arrest disorders (752.4 and 774.5 per 10 000 pregnancies). Conclusions This study generated incidence proportions of pregnancy outcomes and pregnancy-related EIs from the CPRD for different pregnancy cohorts, including low-risk pregnancies. The reported incidence proportions of pregnancy outcomes and pregnancy-related EIs are largely consistent with external estimates. These results may facilitate the interpretation of safety data from maternal immunization trials and the safety monitoring of maternal vaccines. They may also be of interest for any intervention studied in populations of pregnant women.